Measuring disaster resilience in communities and households: Pragmatic tools developed in Australia. Issue 2 (11th April 2016) - Arbon, Paul; Steenkamp, Malinda; Cornell, Victoria; Cusack, Lynette; Gebbie, Kristine
Abstract : Purpose: This paper aims to discuss the development of two toolkits that were designed to help communities and households measure their level of disaster resilience and provide practical tools to help them increase and maintain these levels. Design/methodology/approach: The toolkits were developed across two studies, with the community toolkit development being undertaken first. A literature review was conducted to develop a definition and model of community disaster resilience; and a Scorecard was designed to assess levels of existing community disaster resilience. The definition and Scorecard were reviewed and refined with the help of two communities before a final version was trialled in four communities across Australia. The household toolkit project followed a similar approach, with trialling being undertaken in conjunction with two non-government organisations that carry out outreach work in the community. Findings: The development and trial of the Scorecards was extremely valuable. The conclusion voiced by communities and reached by the study project teams was that the user-friendly Scorecard is a workable tool for people to assess their household and community disaster resilience and to come together to plan what might further strengthen resilience. Critical to the Scorecards' success was an understanding of the purpose of the assessment tool and the meaning of resilience. Originality/value: The toolkits take an all-hazards approach and help community members, individuals and local policymakers to set priorities, allocate funds and develop emergency and disaster management programmes that build local community resilience.